Study of Patients Absconding Behavior in a General Hospital at Southern Region of Iran - Mohammad Khammarnia; Aziz Kassani; Mohammad Reza Amiresmaili; Ahmad Sadeghi; Zahra Karimi Jaberi; Zahra Kavosi (Kerman University of Medical Sciences, 2015)
Background Patients' escape from hospital imposes a significant cost to patients as well as the health system. Besides, for these patients, exposure to adverse events (such as suicide, self-harm, violence and harm to hospital reputation) are more likely to occur compared to others. The present study aimed to determine the characteristics of the absconding patients in a general hospital through a case-control design in Shiraz, Iran. Methods This case-control study was conducted on 413 absconded patients as case and 413 patients as control in a large general hospital in Shiraz, southern Iran. In this study, data on the case and control patients was collected from the medical records using a standard checklist in the period of 2011-3. Then, the data were analyzed using descriptive and analytical statistics, through SPSS 16. Results The finding showed that 413 patients absconded (0.50%) and mean of age in case group was 40.98 ± 16.31 years. In univariate analysis, variables of gender [Odds Ratio (OR)= 2], ward (OR= 1.22), insurance status (OR= 0.41), job status (OR= 0.34) and residence expenditure were significant. However, in multivariate analysis significant variables were age (ORadj= 0.13), gender (ORadj= 2.15), self-employment/unemployed (ORadj= 0.47), emergency/admission (ORadj= 2.14), internal/admission (ORadj= 3.16), insurance status (ORadj= 4.49) and residence expenditure (ORadj= 1.15). Conclusion Characteristics such as middle age, male gender, no insurance coverage, inability to afford hospital expenditures and admission in emergency department make patients more likely abscond from the hospital. Therefore, it may be necessary to focus efforts on high-risk groups and increase insurance coverage in the country to prevent absconding from hospital.